(untitled) (Journal of Chemical Engineering, 2014)
The degradation of Methylene Blue (MB) in aqueous solution has been investigated in a photocatalytic reactor under UV radiation and in presence of zinc oxide (ZnO). The photodegradation kinetics follows pseudo-first order reaction. The effect of process parameters such as catalyst loading and initial concentration of MB on the degradation is investigated. The results show that the degradation rate is affected insignificantly by the increases in the catalyst dosage. Batch test, however, shows that with an increase in the initial concentration the apparent rate constant gradually decreases. The first results with a continuous reactor with a diluted feed solution show inspiring dye removal. DOI: http://dx.doi.org/10.3329/jce.v28i1.18110 Journal of Chemical Engineering, Vol. 28, No. 1, December 2013: 41-44